The Nature of Soft Excess in ESO 362-G18 Revealed by XMM-Newton and NuSTAR Spectroscopy - Xu, Yerong; Garcia, Javier; Walton, Dominic J.; Connors, Riley M. T.; Madsen, Kristin; Harrison, Fiona A. (Astrophysical Journal, 2021)
We present a detailed spectral analysis of the joint XMM-Newton and NuSTAR observations of the active galactic nuclei (AGNs) in the Seyfert 1.5 Galaxy ESO 362-G18. The broadband (0.3-79 keV) spectrum shows the presence of a power-law continuum with a soft excess below 2 keV, iron Kα emission (∼6.4 keV), and a Compton hump (peaking at ∼20 keV). We find that the soft excess can be modeled by two different possible scenarios: a warm (kT e ∼ 0.2 keV) and optically thick (τ ∼ 34) Comptonizing corona, or with a relativistically blurred reflection off a high-density () inner disk. These two models cannot be easily distinguished solely from their fit statistics. However, the low temperature (kT e ∼ 20 keV) and the thick optical depth (τ ∼ 5) of the hot corona required by the warm corona scenario are uncommon for AGNs. We also fit a "hybrid"model, which includes both disk reflection and a warm corona. Unsurprisingly, as this is the most complex of the models considered, this provides the best fit, and more reasonable coronal parameters. In this case, the majority of the soft excess flux arises in the warm corona component. However, based on recent simulations of warm coronae, it is not clear whether such a structure can really exist at the low accretion rates relevant for ESO 362-G18 (˙m∼ 0.015). This may therefore argue in favor of a scenario in which the soft excess is instead dominated by the relativistic reflection. Based on this model, we find that the data would require a compact hot corona (h ∼ 3 R Horizon) around a rapidly spinning (a ∗ > 0.927) black hole.
CRIS-Team Scopus Importer:2021-06-11